Reflections on planning and control of sport training in rhythmic gymnastics - Ilisastigui Avilies, M.; Goeva Diaz, Y.; Ochoa Borras, N. (High performance gymnastics, 2014)
Rhythmic gymnastics is a sport where art and technique are blended, and the gymnasts outcomes depend on the development of those two components, which are expressed in the composition and execution of the competitive exercises. This conjugation depends on several factors, such as the occurrence of these two elements in the composition and execution of competitive exercises. When a gymnast arrives at the stage of 'mastery' (after eight to ten years of systematic training), she already possesses a maximum level of gymnastic technique. Therefore, she is oriented to the improvement of the competitive exercise, in each competitive event program. According to this objective, all the training cycles in rhythmic gymnastics are planned and controlled by the coach, adapting them to the individual strengths and weaknesses of each gymnast (and/or her corresponding team or group). This should be done with regard to the demands manifested in the Code of Points of the Olympic cycle. In this chapter, several characteristics are mentioned that include the planning and the control as a part of the process of training in rhythmic gymnastics. Experiences that emerge from a scientific investigation of a group of Cuban researchers are presented in greater detail.